Novel silicon-carbon negative electrode material and preparation method thereof
By using phenolic resin, boric acid and silicon alloy powder in lithium-ion batteries, the problem of insufficient volume expansion and conductivity of silicon materials is solved, and the high efficiency and long life of the battery are achieved.
Patent Information
- Application Number
- CN202510160112.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-05-30
AI Technical Summary
The existing silicon/carbon anode materials in lithium-ion batteries have poor circulation stability due to the volume expansion of silicon materials and insufficient electronic conductivity, which limits the improvement of silicon content.
A new high-conductivity silicon carbon negative electrode material was prepared by pre-oxidation, high-temperature carbonization and fluidization coating treatment using phenolic resin and boric acid as carbon sources and cross-linking agents.
Effectively improves the first-time Coulomb efficiency and cycle life of the battery, simplifies the process and improves safety.
Smart Images

Figure CN120072888A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anode materials, and particularly to a novel silicon-carbon anode material and a preparation method thereof. Background Art
[0002] With the rapid development of energy storage devices, the demand for high capacity and high power of lithium-ion batteries (LIBs) is becoming increasingly urgent. Silicon / carbon (Si / C) anodes have the advantages of high process compatibility, low cost, and high specific capacity, and are considered promising for next-generation lithium-ion batteries. However, silicon materials will cause significant volume expansion during lithium deintercalation / insertion, and the inherent electronic conductivity of silicon is insufficient. These problems limit the silicon content in Si / C anodes to less than 15 wt%. Maintaining cycle stability while increasing the silicon content is a key challenge in this field. To address the challenges of achieving high-silicon-content electrodes and improving the cycling performance of Si / C anodes, two factors must be considered: cyclic volume expansion and establishing a robust electronic conductive network. Previous studies have proposed various strategies to achieve this goal, including nanosizing and coating. However, the inevitable periodic volume expansion during cycling will cause disconnection between the conductive additive and silicon. In addition, this contact situation may deteriorate with the increase in the number of cycles, ultimately leading to battery failure.
[0003] Patent CN105070894A discloses a porous silicon-based composite anode material for lithium-ion batteries. The anode material has a capsule structure, with the capsule core being amorphous porous silicon and the capsule wall being a conductive carbon material. By setting the capsule core as amorphous porous silicon, it has a larger specific surface area and a rich pore structure, effectively alleviating the volume expansion and contraction effect of silicon during charge and discharge, and improving the comprehensive performance of the material. However, the preparation process of this material is complex, the grinding process has uneven control over the particle size of the material, and the coating density is poor. Patent CN116995220A discloses a silicon-carbon anode material, which uses boric acid to treat a polymer to form a carbon matrix, and silicon deposition is carried out to form a silicon-carbon material. However, the uneven carbonization of the organic polymer material easily leads to poor stability of the carbon material matrix and poor conductivity, and thus poor cycling performance.
[0004] Currently, the silicon anodes used in commercial battery materials are mainly silicon-oxygen anodes, with low capacity and poor cycling performance. Even after simple coating, the conductivity of the material is still poor, and the volume expansion problem still has no good solution. Summary of the Invention
[0005] Based on the technical problems existing in the background art, the present invention proposes a novel silicon-carbon anode material and a preparation method thereof.
[0006] A preparation method of a novel silicon-carbon anode material proposed by the present invention includes the following steps:
[0007] S1. After uniformly mixing phenolic resin in an organic solvent, add boric acid solution, stir and ultrasonicate to obtain Material A;
[0008] S2. Add silicon alloy to Material A and stir evenly to obtain Material B;
[0009] S3. Pre-oxidize and perform high-temperature carbonization on Material B to obtain Material C;
[0010] S4. Wash, filter and dry Material C to obtain Material D;
[0011] S5. After subjecting Material D to fluidized coating treatment, a novel silicon-carbon anode material is obtained.
[0012] The method of the present invention first dissolves phenolic resin in an organic solvent, adds boric acid for ultrasonic dispersion, then adds silicon alloy powder, continuously mixes and stirs, and then places it in a tube furnace for roasting. After low-temperature pre-oxidation by introducing air and then high-temperature carbonization in an inert atmosphere, after discharging, continuous pickling is carried out until no bubbles are generated. After filtration and drying, fluidized secondary carbon coating treatment is carried out to form a novel silicon-carbon anode material with high conductivity. The novel silicon-carbon anode material prepared by the present invention can effectively improve the initial Coulomb efficiency and cycle life of the battery, and has a simple process and high safety.
[0013] Preferably, in S1, the particle size D50 of the phenolic resin is 1 - 8 μm.
[0014] Phenolic resin is a high-quality carbon source with a high residual carbon rate. Controlling the particle size of phenolic resin within a certain range can not only provide a carrier for the silicon source but also limit the volume expansion of silicon.
[0015] Preferably, in S1, the organic solvent is selected from one or more of ethanol, methanol, chloroform, toluene, xylene, and acetone; the mass ratio of phenolic resin to the organic solvent is 1:2 - 1:10.
[0016] Preferably, in S1, the concentration of the boric acid solution is 0.5 - 1 mol / L; the mass ratio of the boric acid solution to the organic solvent is 1:1 - 10:1.
[0017] Boric acid can be added to the resin as a cross-linking agent to promote its hardening, and at the same time, boron doping helps to improve electron and lithium-ion kinetics.
[0018] Preferably, in S1, the stirring speed is 500 - 1000 r / min, the stirring time is 5 - 20 min; the ultrasonic frequency is 50 - 200 Hz, and the ultrasonic time is 10 - 30 min.
[0019] Preferably, in the step S2, the silicon alloy is selected from one or more of aluminum-silicon alloy, tin-silicon alloy, iron-silicon alloy, titanium-silicon alloy, and copper-silicon alloy; the particle size D50 of the silicon alloy is 5-10 μm; the mass ratio of the silicon alloy to the material A is 1:1-1:10; the stirring speed is 300-1000 r / min, and the stirring time is 30-60 min.
[0020] The silicon alloy powder provides a silicon source and forms a porous structure after metal etching, which is beneficial to alleviating the change of internal stress during the lithium deintercalation / insertion process of the material.
[0021] Preferably, in the step S3, the pre-oxidation includes treating at 180-300 °C for 1-3 h in an oxygen-containing gas atmosphere.
[0022] More preferably, the oxygen-containing gas is selected from at least one of air and oxygen.
[0023] The function of pre-oxidation is to increase oxygen-containing functional groups and provide more activated pore-forming sites.
[0024] Preferably, in the step S3, the high-temperature carbonization includes treating at 600-900 °C for 4-12 h in a protective gas atmosphere.
[0025] More preferably, the protective gas is selected from at least one of helium, argon, and nitrogen.
[0026] The function of high-temperature carbonization is to improve the stability of the carbon matrix.
[0027] Preferably, in the step S4, the washing includes acid washing and water washing.
[0028] More preferably, the acid solution for acid washing is selected from at least one of acetic acid solution, hydrochloric acid solution, sulfuric acid solution, and nitric acid solution.
[0029] The function of acid washing is to remove impurity elements introduced during the activated pore-forming process.
[0030] More preferably, the acid solution for acid washing is a mixture of acid and water, and the mass ratio of acid to water is 1:2-1:5.
[0031] More preferably, the mass ratio of the acid solution for acid washing to the material C is 1:1-1:10.
[0032] More preferably, the ratio of water to the material C in water washing is 1:1-10:1.
[0033] Preferably, after washing in the step S4, the pH is 7-8; the drying temperature is 300-400 °C, and the drying time is 2-4 h.
[0034] Preferably, in the step S5, the fluidized coating treatment includes placing the material D in a fluidized bed, introducing a carbon source gas, and maintaining the temperature at 500 - 700 °C for 1 - 6 h.
[0035] More preferably, the carbon source gas is selected from at least one of methane, ethane, and acetylene.
[0036] Fluidized carbon coating can improve the specific surface area and conductivity of the material, alleviate the volume expansion of silicon, and enhance the conductivity of the particles.
[0037] The present invention also provides a novel silicon-carbon anode material prepared by the above preparation method.
[0038] The beneficial effects of the present invention are as follows:
[0039] In the method of the present invention, first, phenolic resin is dissolved in an organic solvent, boric acid is added for ultrasonic dispersion, and then silicon-containing alloy powder is added. After continuous mixing and stirring, it is placed in a tube furnace for roasting. After low-temperature pre-oxidation by introducing air and then high-temperature carbonization by introducing an inert atmosphere, the product is continuously pickled until no bubbles are generated after discharging. After filtration and drying, fluidized secondary carbon coating treatment is carried out to form a novel silicon-carbon anode material with high conductivity. The novel silicon-carbon anode material prepared by the present invention can effectively improve the initial Coulomb efficiency and cycle life of the battery, and has a simple process and high safety. Phenolic resin is a high-quality carbon source with a high char residue rate, which can provide a carrier for the silicon source and limit the volume expansion of silicon. Boric acid can be added to the resin as a cross-linking agent to promote its hardening, and boron doping helps to improve electron and lithium-ion kinetics. The silicon-containing alloy powder provides a silicon source while forming a porous structure after metal etching, which is beneficial to alleviating the change of internal stress during lithium deintercalation / insertion of the material. Fluidized secondary carbon coating can improve the specific surface area and conductivity of the material, alleviate the volume expansion of silicon, and enhance the conductivity of the particles. Description of the Drawings
[0040] Figure 1 It is a scanning electron microscope image of the novel silicon-carbon anode material prepared in Example 1 of the present invention.
[0041] Figure 2 It is the cross-section cutting test result of the novel silicon-carbon anode material prepared in Example 1 of the present invention.
[0042] Figure 3 It is the charge-discharge capacity test result of the novel silicon-carbon anode material prepared in Example 1 of the present invention and the commercial SiO / C material of Comparative Example 1.
[0043] Figure 4 It is the cycle performance test result of the novel silicon-carbon anode material prepared in Example 1 of the present invention and the commercial SiO / C material of Comparative Example 1. Detailed Embodiments
[0044] The technical solution of the present invention is described in detail through specific embodiments.
[0045] The materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources without special instructions.
[0046] Example 1
[0047] A preparation method of a novel silicon-carbon anode material includes the following steps:
[0048] S1. Add 50 g of phenolic resin with a particle size D50 of 1 μm to a beaker containing 150 g of absolute ethanol, then add 150 g of 1 mol / L boric acid solution, stir for 20 min and then ultrasonically disperse for 10 min to obtain material A;
[0049] S2. Add 35 g of aluminum-silicon alloy powder to material A, and then stir with a high-speed mixer at a rotation speed of 500 r / min for 60 min to obtain material B;
[0050] S3. Transfer material B to a tubular furnace, introduce oxygen, heat at 300 °C for 1 h, then introduce argon, heat to 800 °C, sinter for 4 h, and cool to obtain material C;
[0051] S4. Place 100 g of material C and 100 g of hydrochloric acid in 200 g of deionized water, stir and react for 2 h, filter, add to 300 g of deionized water, stir and react for 2 h and then filter, repeat the water washing step until the pH after washing is 7, put it into a box furnace, heat at 300 °C for 4 h to obtain material D;
[0052] S5. Place material D in a fluidized bed, introduce acetylene and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 600 °C for 2 h, and cool to obtain the product.
[0053] Example 2
[0054] A preparation method of a novel silicon-carbon anode material includes the following steps:
[0055] S1. Add 50 g of phenolic resin with a particle size D50 of 4 μm to a beaker containing 150 g of acetone, then add 150 g of 1 mol / L boric acid solution, stir for 20 min and then ultrasonically disperse for 10 min to obtain material A;
[0056] S2. Add 35 g of aluminum-silicon alloy powder to material A, and then stir with a high-speed mixer at a rotation speed of 500 r / min for 60 min to obtain material B;
[0057] S3. Transfer material B to a tubular furnace, introduce oxygen, heat at 300 °C for 1 h, then introduce argon, heat to 800 °C, sinter for 4 h, and obtain material C after cooling;
[0058] S4. Place 100 g of material C and 100 g of hydrochloric acid in 200 g of deionized water, stir and react for 2 h, filter, add to 300 g of deionized water, stir and react for 2 h and then filter, repeat the water washing step until the pH after washing is 7, put it into a box furnace, heat at 300 °C for 4 h to obtain material D;
[0059] S5. Place material D in a fluidized bed, introduce acetylene and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 600 °C for 2 h, and obtain the product after cooling.
[0060] Example 3
[0061] A preparation method of a novel silicon-carbon anode material, comprising the following steps:
[0062] S1. Add 50 g of phenolic resin with a D50 particle size of 6 μm to a beaker containing 200 g of absolute ethanol, then add 400 g of 1 mol / L boric acid solution, stir for 20 min and then ultrasonically disperse for 10 min to obtain material A;
[0063] S2. Add 130 g of aluminum-silicon alloy powder to material A, and then stir with a high-speed stirrer at a rotation speed of 1000 r / min for 30 min to obtain material B;
[0064] S3. Transfer material B to a tubular furnace, introduce oxygen, heat at 400 °C for 1 h, then introduce argon, heat to 900 °C, sinter for 6 h, and obtain material C after cooling;
[0065] S4. Place 200 g of material C and 200 g of hydrochloric acid in 1000 g of deionized water, stir and react for 2 h, filter, add to 1000 g of deionized water, stir and react for 2 h and then filter, repeat the water washing step until the pH after washing is 7, put it into a box furnace, heat at 300 °C for 4 h to obtain material D;
[0066] S5. Place material D in a fluidized bed, introduce methane and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 700 °C for 2 h, and obtain the product after cooling.
[0067] Example 4
[0068] A preparation method of a novel silicon-carbon anode material, comprising the following steps:
[0069] S1. Add 200 g of phenolic resin with a D50 particle size of 8 μm to a beaker containing 600 g of xylene, then add 1200 g of 1 mol / L boric acid solution, stir for 10 min and then ultrasonically disperse for 20 min to obtain Material A;
[0070] S2. Add 100 g of aluminum-silicon alloy powder to Material A, and then stir with a high-speed mixer at a rotation speed of 700 r / min for 40 min to obtain Material B;
[0071] S3. Transfer Material B to a tubular furnace, introduce oxygen, heat at 350 °C for 2 h, then introduce nitrogen, heat to 600 °C, sinter for 6 h, and cool to obtain Material C;
[0072] S4. Place 100 g of Material C and 100 g of hydrochloric acid in 200 g of deionized water, stir and react for 2 h, filter, add to 300 g of deionized water, stir and react for 2 h and then filter, repeat the water washing step until the pH after washing is 7, put it into a box furnace, heat at 300 °C for 4 h to obtain Material D;
[0073] S5. Place Material D in a fluidized bed, introduce acetylene and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 600 °C for 2 h, and cool to obtain the product.
[0074] Comparative Example 1
[0075] Comparative Example 1 is a commercial SiO / C material.
[0076] Comparative Example 2
[0077] A preparation method of a silicon-carbon anode material, comprising the following steps:
[0078] S1. Add 50 g of phenolic resin with a D50 particle size of 1 μm to a beaker containing 150 g of absolute ethanol, stir for 20 min and then ultrasonically disperse for 10 min to obtain Material A;
[0079] S2. Add 35 g of aluminum-silicon alloy powder to Material A, and then stir with a high-speed mixer at a rotation speed of 500 r / min for 60 min to obtain Material B;
[0080] S3. Transfer Material B to a tubular furnace, introduce oxygen, heat at 300 °C for 1 h, then introduce argon, heat to 800 °C, sinter for 4 h, and cool to obtain Material C;
[0081] S4. Place 100 g of Material C and 100 g of hydrochloric acid in 200 g of deionized water, stir and react for 2 h, filter, add to 300 g of deionized water, stir and react for 2 h and then filter. Repeat the water washing step until the pH after washing is 7. Place it in a box furnace, heat at 300 °C for 4 h to obtain Material D;
[0082] S5. Place Material D in a fluidized bed, introduce acetylene and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 600 °C for 2 h, and obtain the product after cooling.
[0083] Comparative Example 3
[0084] A preparation method of a silicon-carbon anode material, comprising the following steps:
[0085] S1. Add 50 g of phenolic resin with a D50 particle size of 4 μm to a beaker containing 150 g of absolute ethanol, stir for 20 min and then ultrasonically disperse for 10 min to obtain Material A;
[0086] S2. Add 35 g of aluminum-silicon alloy powder to Material A, and then stir with a high-speed stirrer at a rotation speed of 500 r / min for 60 min to obtain Material B;
[0087] S3. Transfer Material B to a tubular furnace, introduce argon, heat to 800 °C, sinter for 4 h, and obtain Material C after cooling;
[0088] S4. Place 100 g of Material C and 100 g of hydrochloric acid in 200 g of deionized water, stir and react for 2 h, filter, add to 300 g of deionized water, stir and react for 2 h and then filter. Repeat the water washing step until the pH after washing is 7. Place it in a box furnace, heat at 300 °C for 4 h to obtain Material D;
[0089] S5. Place Material D in a fluidized bed, introduce acetylene and nitrogen, with an acetylene flow rate of 3 L / min and a nitrogen flow rate of 12 L / min, heat and sinter at 600 °C for 2 h, and obtain the product after cooling.
[0090] Test Example
[0091] Perform a scanning electron microscope test on the novel silicon-carbon anode material prepared in Example 1, and the results are as Figure 1 shown. Perform a cross-section cutting test, and the results are as Figure 2 shown. It can be seen from Figures 1 - 2 that the particle size of the novel silicon-carbon anode material prepared in Example 1 is relatively uniform, and the particle size is about 1 μm. Compare the conductivity of the materials in Example 1 and Comparative Example 1, as Figure 3 shown.
[0092] The silicon-carbon anode materials of Examples 1 to 4 and Comparative Examples 2 to 3, and the commercial SiO / C material of Comparative Example 1 were used as anode active materials respectively. Slurries were prepared and coated according to the mass ratio of anode active material: conductive agent SP: binder LA133 of 8:1:1, and CR2016 button cells were assembled. The electrolyte used was an EC+DMC solution of 1 mol / L LiPF6, and electrochemical performance tests were carried out. Using NCM811 as the cathode and the anode materials prepared in Comparative Example 1 and Example 1 as the anode, the processes of slurry preparation, coating, rolling, slitting, die-cutting, stacking, welding electrode tabs, top and side sealing, baking, liquid injection, etc. were carried out to assemble 7 Ah soft-pack batteries. After formation and grading, room temperature cycle tests were carried out at a current density of 1C / 1C. The test results are shown in Table 1 and Figures 3 - 4 as follows.
[0093] Table 1
[0094]
[0095]
[0096] It can be seen from the data in Table 1 that the batteries assembled with the novel silicon-carbon anode material prepared in the present invention have a higher first discharge specific capacity, first charge specific capacity, and first Coulombic efficiency, and have excellent cycle performance.
[0097] In summary, the novel silicon-carbon anode material provided by the present invention can effectively improve the first Coulombic efficiency and cycle life of the battery.
[0098] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a novel silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1, adding phenolic resin to an organic solvent and mixing evenly, adding boric acid solution, stirring, and ultrasonicating to obtain material A; S2, adding silicon alloy to material A, stirring evenly to obtain material B; S3, pre-oxidizing and high-temperature carbonizing material B to obtain material C; S4, washing, filtering and drying material C to obtain material D; S5. After subjecting material D to fluidized coating treatment, a new silicon-carbon negative electrode material is obtained.
2. The preparation method according to claim 1, characterized in that: In the S2, the silicon alloy is selected from one or more of aluminum silicon alloy, tin silicon alloy, iron silicon alloy, titanium silicon alloy, and copper silicon alloy; the particle size D50 of the silicon alloy is 5 to 10 μm; and the mass ratio of the silicon alloy to the material A is 1:1 to 1:
10.
3. The preparation method according to claim 1, characterized in that: In the S1, the particle size D50 of the phenolic resin is 1 to 8 μm; the organic solvent is selected from one or more of ethanol, methanol, chloroform, toluene, xylene, and acetone; and the mass ratio of the phenolic resin to the organic solvent is 1:2 to 1:
10.
4. The preparation method according to claim 1, characterized in that: In the S1, the concentration of the boric acid solution is 0.5-1 mol / L; the mass ratio of the boric acid solution to the organic solvent is 1:1-10:
1.
5. The preparation method according to claim 1, characterized in that: In the above-mentioned S3, the pre-oxidation comprises a treatment in an oxygen-containing gas atmosphere at 180-300° C. for 1-3 hours; the oxygen-containing gas is selected from at least one of air and oxygen.
6. The preparation method according to claim 1, characterized in that: In the above-mentioned S3, the high temperature carbonization comprises treating in a protective gas atmosphere at 600-900° C. for 4-12 hours; the protective gas is selected from at least one of helium, argon and nitrogen.
7. The preparation method according to claim 1, characterized in that: In the above-mentioned S4, washing includes pickling and water washing; the acid solution for pickling is selected from at least one of acetic acid solution, hydrochloric acid solution, sulfuric acid solution and nitric acid solution.
8. The preparation method according to claim 1, characterized in that: In the above-mentioned S5, the fluidized coating treatment includes placing the material D in a fluidized bed, introducing a carbon source gas, and keeping the temperature at 500-700° C. for 1-6 hours; the carbon source gas is selected from at least one of methane, ethane, and acetylene.
9. A new type of silicon-carbon negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Porous silicon-based composite anode material for lithium ion battery and preparation method and application
CN105070894A
Silicon-carbon negative electrode material and preparation and application thereof
CN116995220A
Cited By
Amorphous carbon coated silicon composite material and preparation method thereof
CN120914221A